2021
DOI: 10.1021/acs.nanolett.0c04368
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Dephasing Dynamics in MoS2

Abstract: A variety of quantum degrees of freedom, e.g., spins, valleys, and localized emitters, in atomically thin van der Waals materials have been proposed for quantum information applications, and they inevitably couple to phonons. Here, we directly measure the intrinsic optical phonon decoherence in monolayer and bulk MoS 2 by observing the temporal evolution of the spectral interference of Stokes photons generated by pairs of laser pulses. We find that a prominent optical phonon mode E 2g exhibits a room-temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Coherent phonon dephasing is an important process for understanding the light–matter interaction process and is related to quantum photonic applications. 46,47…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coherent phonon dephasing is an important process for understanding the light–matter interaction process and is related to quantum photonic applications. 46,47…”
Section: Resultsmentioning
confidence: 99%
“…Coherent phonon dephasing is an important process for understanding the light-matter interaction process and is related to quantum photonic applications. 46,47 For the time delay of up to 1.3 ps, the NVRB continues to have an influence on the CARS signal. After the transition from dip to peak, we model the dephasing process as a sudden stimulation in delay time T 0 and decay exponentially with a dephasing time constant…”
Section: Phonon Dephasing Of the Lozo′ Modementioning
confidence: 99%
“…Phonon describes the lattice vibration with different frequencies [43,[95][96][97][98]. Then, the phonons dissipate their energy through ultrafast processes such as electron-phonon scattering [99], phonon diphase [100], and exciton-phonon coupling [101], which determine the phonon lifetime. Ding et al [102] found that the energy accumulated in the adhesion stage and completely dissipated within 100 ps by the excitation of phonons at the Cu interface.…”
Section: Ultrafast Phonon Energy Dissipation Dynamicsmentioning
confidence: 99%
“…14 However, the main limitation of using these defects is the optical decoherence due to exciton−phonon coupling and spin noise. 15,16 So far, most of the basal plane defect engineering is reported either by double-step hydrothermal, annealing, and etching or by the doping method. 17−19 However, systematic evolution of defects under sulfur-deficit to sulfur-rich conditions is not well explored.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Apart from catalytic activity, the defects of MoS 2 in the 2D counterpart have also been demonstrated as the potential sources of the quantum emitter in the field of quantum information technology . However, the main limitation of using these defects is the optical decoherence due to exciton–phonon coupling and spin noise. , So far, most of the basal plane defect engineering is reported either by double-step hydrothermal, annealing, and etching or by the doping method. However, systematic evolution of defects under sulfur-deficit to sulfur-rich conditions is not well explored.…”
Section: Introductionmentioning
confidence: 99%